TERMOS NEOLÓGICOS FORMADOS PELO SUFIXO -ADO NA OBRA DE VANDELLI (1788) - KAMILA DA SILVA BARBOSA (2023)
The "Diccionario dos Termos Technicos de Historia Natural", published in Coimbra in 1788, is an important work for the history of Portuguese science. The work of the Italian author Domingos Vandelli is a dictionary that contains translations of the Latin technical terms of the Natural Sciences used by Linnaeus, an important Swedish naturalist, with the target audience being students of Natural Sciences at the University of Coimbra. This work is of great importance, both for the study of the beginnings of Natural Sciences, in relation to the accessibility of scientific terms previously available only in Latin, and for the scientific vocabulary in Portuguese, since, in search of the translation/definition of terms from Latin and the lack of equivalents in Portuguese, the author created neologisms for the elaboration of translations and definitions. Thus, aiming to contribute to the study of the Portuguese scientific lexicon, this work aims to carry out a study of the neological terms of the scientific Portuguese of the 18th century formed through suffix derivation - here represented by the suffix -ado. For that, the concepts of Etymology, Morphology, Neology and Terminology were used. Thus, the following specific objectives were established: a) to analyze the terms in order to describe the process of neological creation that gave rise to them; b) produce etymological hypotheses through the analysis of the data found; thus counting on the following steps: (i) collect the terms in Portuguese formed by the suffix -ado; (ii) verify the dates prior to Vandelli's work (1788) for such terms in the Houaiss Dictionary of the Portuguese Language, in order to be able to classify them as neologisms or not; (iii) check whether the terms have fallen into disuse or are still used; (iv) elaborate the definitions of the terms according to the meaning they had at the time of the "Diccionario dos Termos Tecnicos de Historia Natural" and its etymological hypothesis. With that, it was possible to identify how the terms were inserted in the Portuguese language, being able to be classified in: 1. Neologisms created through the calque process (being “literal” calques and calques with recovery of the Latin form); 2. Neologisms with double possibility of analysis (derivation and calque; derivation or form of participle) and 3. Neologisms formed only by derivation. This study stresses the influence of Latin in scientific terminology and in the historical formation of Portuguese terms.